Agent system for plant-soil-environment interactions - Wang, Feiqi (2015)
This research aims to study how to build a multi-agent system to simulate how roots grow in the soil environment. The area of this research include the intelligent agent, agent-based modelling, modelling biological system, convolution algorithm and some knowledge about botany. The multi-agent system consists of the main root agent and lateral root agent. The result of the simulation and environment will be demonstrated by 3D model. Some value of simulation can be changed in GUI.